O teatro é um divã: psicoterapia teatral e sua contribuição para melhoria do desempenho escolar - SILVA, Antonio Carlos de Souza (2021)
This work aims to investigate the existence of a particular aspect of theater beyond conventionality. A dimension focused on therapeutic vision. It analyzes the systematics that make theater-therapy possible, its applications both in the clinical scope, but especially in the educational field. It verifies the relation with a variant of pedagogy, psycho-pedagogy and possible contributions to this field of knowledge. Finally, it analyzes a proposal of insertion of insertion of this potentiality with purpose to the school improvement.